Hepatocytic Insufficiency - V. I. Reshetnyak (Общая реаниматология, 2005)
The lecture deals with hepatocytic insufficiency, one of the urgent problems in modern clinical medicine. It also considers the major clinical signs of hepatocytic insufficiency and the mechanisms of their development, as well as the principles of treatment of its major symptoms and syndromes.